ANALISIS ISI PEMBERITAAN BENCANA SITU GINTUNG DI CIREUNDEU, TANGERANG, BANTEN PADA SURAT KABAR HARIAN KOMPAS PERIODE BULAN MARET-APRIL 2009 - Taufik Muharfan; Arif Wibawa; Retno Hendariningrum (Jurnal Ilmu Komunikasi, 2009)
An earthquake occurred on Tangerang, Banten around at 3 a.m. Many water debit from torrential rain on Cirendeu village causes broken down of dike which build more or less 10 meters in 1930s. There are 100 people died effect of water knocking more or less 4 meters to citizen housing that was sleeping. Many reactions appeared after that incident, minimum government concern about dike caring becomes topic for Indonesian society at that moment. The result showed that news of broken down Situ Gintung dike at Kompas daily newspaper appears on inside pages (not headline). The informant that often appears in both of daily newspaper was combination between victims and government. News type that used in Kompas was straight news. Coverage type used in Kompas was two sides, while in Jawa Pos was one side. News orientation in Kompas were combination between psychologist and sociologist. Fact collection technique used in Kompas was interview. Combination analysis unit of news characteristic in Kompas was argumentative and descriptive. New dimension in Kompas daily newspaper was combination between social and politic.